2019
DOI: 10.1101/2019.12.23.887109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lipin-1 contributes to IL-4 mediated macrophage polarization

Abstract: ABSTRACTMacrophage responses contribute to a diverse array of pathologies ranging from infectious disease to sterile inflammation. Polarization of macrophages determines their cellular function within biological processes. Lipin-1 is a phosphatidic acid phosphatase in which its enzymatic activity contributes to macrophage pro-inflammatory responses. Lipin-1 also possesses transcriptional co-regulator activity and whether this activity is required for macrophage polarization is … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Mice lacking lipin-1 enzymatic activity in myeloid cells (Lipin-1mEnzy KO) had reduced plaque size compared to wild type mice suggesting lipin-1 enzymatic activity is atherogenic [1]. In contrast, we have demonstrated that lipin-1 transcriptional coregulatory activity likely promotes wound healing responses in macrophages [24]. Figure 1: Lipin-1 localizes to the nucleus in bone marrow-derived macrophages Femurs were isolated from wild type mice.…”
Section: Lipin-1 Transcriptional Co-regulatory Activity Is Involved Imentioning
confidence: 92%
See 4 more Smart Citations
“…Mice lacking lipin-1 enzymatic activity in myeloid cells (Lipin-1mEnzy KO) had reduced plaque size compared to wild type mice suggesting lipin-1 enzymatic activity is atherogenic [1]. In contrast, we have demonstrated that lipin-1 transcriptional coregulatory activity likely promotes wound healing responses in macrophages [24]. Figure 1: Lipin-1 localizes to the nucleus in bone marrow-derived macrophages Femurs were isolated from wild type mice.…”
Section: Lipin-1 Transcriptional Co-regulatory Activity Is Involved Imentioning
confidence: 92%
“…The plaque size in the lipin-1m KO mice was nearly twice as large as the littermate control mice. Lipin-1m KO macrophages had decreased pro-resolving, wound healing macrophage polarization [24]. We hypothesized that myeloid-associated lipin-1 transcriptional co-regulatory activity promotes anti-inflammatory responses within the atherosclerotic plaque.…”
Section: Increased Expression Of Collagen and Pro-inflammatory Genes mentioning
confidence: 99%
See 3 more Smart Citations